Exploring the use of expanded erythroid cells for autologous transfusion for anemia of prematurity. Issue 12 (22nd March 2013) - Khodabux, Chantal M.; van, Yvette; Slot, Manon C.; Bakker‐Verweij, Margreet; Giordano, Piero C.; Brand, Anneke
<x xml:space="preserve">Abstract</x> Background Autologous cord blood (CB) red blood cells (RBCs) can partly substitute transfusion needs in premature infants suffering from anemia. To explore whether expanded CB cells could provide additional autologous cells suitable for transfusion, we set up a simple one‐step protocol to expand premature CB cells. Study Design and Methods CB buffy coat cells and isolated CD34‐positive (CD34pos) cells from premature and full‐term CB and adult blood were tested with several combinations of growth factors while omitting xenogeneic proteins from the culture medium. Cell differentiation was analyzed serially during 21 days using flow cytometry, progenitor assays, and high‐performance liquid chromatography. Results Expanded CB buffy coat cells resulted in a threefold higher number of erythroblasts than the isolated CD34pos cells. However, the RBCs contaminating the buffy coat remained present during the culture with uncertain quality. Premature and full‐term CB CD34pos cells had similar fold expansion capacity and erythroid differentiation. With the use of interleukin‐3, stem cell factor, and erythropoietin, the fold increases of all CD34poscell sources were similar: CB 3942 ± 1554, adult peripheral mobilized blood 4702 ± 1826, and bone marrow (BM) 4143 ± 1908. The proportion of CD235a expression indicating erythroblast presence on Day 21 was slightly higher in the adult CD34pos cell sources: peripheral blood stem cells (96.7 ± 0.8%) and BM (98.9 ± 0.5%) compared to CB (87.7 ± 2.7%; p = 0.002). We were not able to induce further erythroid maturation in vitro. Conclusion This explorative study showed that fairly pure autologous erythroid‐expanded cell populations could be obtained by a simple culture method, which should be optimized. Future challenges comprise obtaining ex vivo enucleation of RBCs with the use of a minimal manipulating approach, which can add up to autologous RBCs derived from CB in the treatment of anemia of prematurity.